Development of English Instructional Model for Communication of Lower Secondary School Students - Varatiporn, Varaporn; Nilnopakoon, Phithack; Kongthong, Usa (Ratchaphruek Journal, 2015)
The objectives of this research were to 1) study language communicative ability factors, 2) develop a communicative language instructional model, and3) studythe effects of a communicative language instructional model. The research procedure consisted of 3 phases: Phase 1, study about language communicative ability factors. A group of samples used in this study were 400 ninth grade students in Lop Buri province. The instruments used in this study were interviews and questionnaires with a reliability of 0.96 were used in statistical data analysis, Phase 2, develop a communicative language instructional model. The model developed is appropriate and contained its feasibility to be used in developing the communicative ability and Phase 3, studythe effects of a communicative language instructional model. The experimental research methodology was conducted by using the time-series research design. The samples of this research were 60 ninth grade students of Winitsuksa School in Lopburi province. Simple random sampling was used to divide students into 2 groups, 30 students equally in control and experimental groups. The data were collected by the English language communication test and satisfaction in the teaching of English to enhance the communication skills of students. The statistics used for data analysis were mean, standard deviation, and statistics, one-way analysis of variance with repeated measures (Repeated Measures One-Way ANOVA). The results were as follows: 1. The confirmatory factor of language communicative ability consisted of 5 components as follows: 1) grammatical competence, 2) sociolinguistic competence, 3) discourse competence, 4) strategic competence, and 5) meta-cognitive competence. The validity of the analysis can be represented by the IOC, and Chi - Square was 191.398. 2. The communicative language instructional model was developed. The teaching has 5 stages: 1) warm-up, 2) presentation, 3) practice, 4) self-assessment and production, and 5) the English language communication test and satisfaction in the teaching of English. 3. The experiment group showed higher scores than the control group at a statistically significant .05 level (F=893.27) and the communicative language instructional model was at the highest level of satisfaction.